PENGARUH PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP SIKAP PEDULI LINGKUNGAN PADA MATERI PENCEMARAN LINGKUNGAN - Fitriati, Mariza; Sahputra, Rachmat; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstrack The aims of this study were to determine whether there was differences of environmental care attitudes between students who was tought by using environment-based learning and students who was tought by using conventional methods and also to determine the effect of environment-based learning towards students’ environmentalcare attitude in environmental pollution course at SMP 13 Pontianak. This research was a quasi eksperimentalwith nonequivalent control groupdesign. Sampling technique by using random sampling . The tools of data collectionwere questionnaire and interview. The environmental care attitude was analayzedusing the U-Mann Whitney test. There was difference of environmental care attitude between studentswho was tougt by using environment-based learning and students who was tought by using conventional methods.Environtment-based learning influenced 29,1% on behavioral caring of environtment of student of class VII SMP 13 Pontianak. Keywords:Environment-Based Learning, Environmental CareAttitude Environmental Poluttion Course Study